2019
DOI: 10.3390/s19030611
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Porosity Distribution during an Erosion Test Using a Coaxial Line Cell

Abstract: The detection of porosity changes within a soil matrix caused by internal erosion is beneficial for a better understanding of the mechanisms that induce and maintain the erosion process. In this paper, an electromagnetic approach using Spatial Time Domain Reflectometry (STDR) and a transmission line model is proposed for this purpose. An original experimental setup consisting of a coaxial cell which acts as an electromagnetic waveguide was developed. It is connected to a transmitter/receiver device both measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A schematic of the experimental setup is provided in Figure 1. A detailed description of the experimental apparatus (including calibration and validation) has been presented in Bittner et al (2019). A brief summary of the apparatus is presented below, as this paper focusses on the application of the coaxial erosion cell to investigate the mixing process in filtration experiments.…”
Section: Coaxial Erosion Cellmentioning
confidence: 99%
See 4 more Smart Citations
“…A schematic of the experimental setup is provided in Figure 1. A detailed description of the experimental apparatus (including calibration and validation) has been presented in Bittner et al (2019). A brief summary of the apparatus is presented below, as this paper focusses on the application of the coaxial erosion cell to investigate the mixing process in filtration experiments.…”
Section: Coaxial Erosion Cellmentioning
confidence: 99%
“…The third step is the conversion of the dielectric permittivity profile to a porosity profile, n(x), using theoretical mixing equations. Prior studies indicated the applicability of the Lichtenecker-Rother model (Bittner et al, 2017(Bittner et al, , 2019 for saturated glass beads, where the dielectric permittivity of the mixture is computed as the weighted sum of the dielectric permittivity of the water and glass beads by their respective volume fraction:…”
Section: Coaxial Erosion Cellmentioning
confidence: 99%
See 3 more Smart Citations